PENGEMBANGAN FOCUS GROUP DISCUSION P. PRAMUKA, KABUPATEN KEPULAUAN SERIBU DALAM RANGKA PENGUATAN EKOWISATA BERKELANJUTAN - Kohar Sulistyadi; Nugroho B Sukamdani; Nelson Pardede (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2017)
In the development of Focus Group Discusion (FGD) ecotourism P. Pramuka, at Kepulauan Seribu District shows the difference of public expectation, the facilities provided by the Government and the desire of tourists as measured on the basis of benefts and interests of all stakeholders. Focus Group Discussion (FGD) attempts to capture the various proposals of the participants in the discussion, but often to analyze the root of the problem and the solution does not include the identifcation of needs in analyzing. As a result the discussion becomes unfocused and becomes diffcult to fnd the root of the problem, and ultimately there is no fundamental solution. To trace the problem and able to give a realistic suggestion can be used as a solution to do the method of Problem Root Analysis and Solution (MAAMS) which presents a way of thinking with supported ï¬‚ow charts to get the best solution. The application of the MAAMS, guides researchers in inductive or deductive, qualitative and quantitative thinking, in greater depth and comprehensiveness, facilitating multi-disciplinary cooperation. The fnal result of this research is able to give consensus solution to synergize each other to catch the opportunity by welcoming the coming of ekowisatawan which keep increasing and fnally able to improve prosperity of society around P Pramuka, Kepulauan Seribu District